STUDI KRITIS TERHADAP PENDIDIKAN SEKULER - Al Azhar; Bahaking Rama, Moh. Natsir Mahmud (ADISAM PUBLISHER, 2025)
Education is a basic need for every human being. The aim of education is to shape humans so they are able to adapt in their lives, by developing the various potentials that exist within them. In the educational process, various views are faced, including understanding related to secular thinking in the world of education. In this paper the author will discuss and criticize secular education. Education in the current era is experiencing various challenges ranging from secularism to implementing the noble values of religious teachings in social life. Muslims are very pragmatic, and even tend to be opportunistic. Secular Ideas in today's life are presented and packaged in a beautiful way through globalization and modernization, which is in line with the development of Western civilization. Secularism is an ideology that seeks to eliminate religious values that originate from revelation in world life, or separate religious life from the world which is actually different from the aim of education, namely forming a pious human spirit